(untitled) (Jurnal Pertanian Terpadu, 2025)
One of the key factors in food security was the role of farmers as producers of agricultural products. However, Bappenas projected that by 2063, the farming profession in Indonesia would cease to exist. This challenges in farmer regeneration was caused by the low interest of the younger generation in entering the agricultural sector, due to the stigma that agriculture is associated with dirty work, poverty, and marginalized communities. Sustainable supply chains can be defined as management systems that integrated responsible practices across three pillars which is economic, environmental, and social throughout the entire product life cycle. Such systems had the potential to increase the participation of young people in agriculture by improving the social and economic status of farmers. Nevertheless, inefficiencies within sustainable agricultural supply chains still occurs, leading to waste, exacerbating inequality, and weakening food security. Therefore, it was necessary to identify the challenges in implementing sustainable agricultural supply chains in Indonesia in order to formulate strategies that could increase their adoption. This study employed in-depth interviews with 15 farmers who had implemented sustainable agricultural supply chain systems. The findings revealed three distinct actor roles and characteristics within the sustainable agricultural supply chain in Indonesia. The suggested strategy was to manage and position each actor according to their function within the system. This approach allowed for the optimization of actor roles, particularly those who served as innovators, in order to promote the broader adoption of sustainable supply chain practices.